Nilai Sosial dalam Cerpen Ngantén Karya Komang Adnyana - Saleh, Ifrado M; Suardiana, I Wayan; Duana Sutika, I Nyoman (Dharma Sastra : Jurnal Penelitian Bahasa dan Sastra Daerah, 2025)
This research, titled "Social Values in Komang Adnyana's Short Story 'Ngantén'," delves into a specific short story, "Ngantén." This particular piece is one of the many compelling titles found within the "Métek Bintang " short story collection. The themes explored in "Métek-Bintang" are remarkably diverse and engaging, encompassing contemporary issues such as transgender identity, LGBTQ+ concerns, child trafficking, and numerous other fascinating topics that significantly enrich modern Balinese literature. The primary objective of this analysis is to ascertain the social values embedded within the chosen short story. To achieve this, the study employed a methodical approach, dividing its research techniques into three distinct stages. Data provision involved observation and careful reading, complemented by translation techniques to ensure accurate comprehension, and meticulous note-taking. The subsequent data analysis phase utilized a qualitative method, supported by descriptive analytical techniques to thoroughly interpret the findings. Finally, the presentation of the analysis results was conducted using an informal method for clear communication. This research specifically adopted a sociology of literature approach to examine the interplay between the literary work and its societal context. The findings reveal the presence of five key social values within the short story: religious values, mutual assistance, forgiveness, compassion, and responsibility